Heyde’s Syndrome - a comprehensive review - Adaśko, Grzegorz; Świda, Michał; Bazarewicz, Jakub; Kubuj, Cezary; Mazur, Urszula; Dmowski, Daniel; Michalska, Anna Teresa; Ogonowska, Paulina; Waszak, Julia; Siwik, Marcin (Quality in Sport, 2025)
Introduction: The objective of this review is to provide a comprehensive overview of the current state of knowledge about Heyde’s syndrome, including its etiology, clinical symptoms, imaging and laboratory findings. The issue of potential complications is raised. Moreover, treatment strategies are introduced. Materials and methods: A review of the literature was conducted through PubMed database to identify articles related to Heyde’s Syndrome using following keywords: “Heyde’s syndrome’’, “acquired von Willebrand disease”, “aortic stenosis”, “gastrointestinal bleeding”. Summary: Heyde’s syndrome is a rare disorder characterized by the triad of aortic stenosis, acquired coagulopathy, and anemia due to recurrent bleeding from gastrointestinal dysplasia. Diagnosis is based on positive results in combined tests such as colonoscopy with the presence of angiodysplasia, echocardiogram showing aortic stenosis, and screening tests for von Willebrand syndrome type 2A. The main treatment is the replacement of the aortic valve, either by surgery or by TAVI. Conclusions: Awareness of Heyde’s syndrome is important for its proper identification and treatment. The management of this disease requires the teamwork of physicians from different specialties.